2009
DOI: 10.1186/1550-2783-6-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of betaine supplementation on power performance and fatigue

Abstract: Background: The purpose of this study was to examine the efficacy of 15 days of betaine supplementation on muscle endurance, power performance and rate of fatigue in active collegeaged men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
97
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(109 citation statements)
references
References 23 publications
4
97
8
Order By: Relevance
“…However, the number of repetitions to exhaustion performed in the squat and bench press exercise was unchanged. Hoffman et al (2009) also reported improvements in muscle endurance in the squat exercise, and increase in the quality of repetitions performed (e.g., number of repetitions performed at 90% of 1-RM) following 2 weeks of betaine supplementation in physically active males. In contrast, no differences in power assessments were noticed.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, the number of repetitions to exhaustion performed in the squat and bench press exercise was unchanged. Hoffman et al (2009) also reported improvements in muscle endurance in the squat exercise, and increase in the quality of repetitions performed (e.g., number of repetitions performed at 90% of 1-RM) following 2 weeks of betaine supplementation in physically active males. In contrast, no differences in power assessments were noticed.…”
Section: Introductionmentioning
confidence: 92%
“…The main physiological function of betaine is either as an organic osmolyte to protect cells under stress or as a catabolic source of methyl groups via transmethylation (Craig 2004). Moreover, there is an evidence indicating that the potential ergogenic value of betaine in athletic performance, especially in strength parameters (Lee et al 2010;Hoffman et al 2009;Maresh et al 2008).…”
Section: Introductionmentioning
confidence: 98%
“…This supports the two important factors from the current study; subjects are doing the exercise correctly by moving both sides similarly for both exercises, and the device detected the similar velocity pattern of both arms. Unlike wired devices to measure velocities [3][4][5] , the wireless inertia sensor is capable of measuring velocity and power of many DB exercises along with body weight exercises such as push-ups and jumps, or others like kettlebell swing, medicine ball throws, etc. Wired devices are only capable of tracking velocity and power from the exercises that are attachable to the bar.…”
Section: Discussionmentioning
confidence: 99%
“…With competing technologies, measurements are taken using a wired device such as Tendo-unit (Tendo Sport machine, Slovak Republic) and GymAware (Kinetic Performance, Australia) in both laboratory and weight room environment. [3][4][5] While these wired devices have their importance, given a capability to provide immediate feedback, the fact that a wire or cord must run between the device and the bar may limit the exercises that can be measured. The wireless inertia sensor, transmitting via Bluetooth™, may provide useful measures in the training environment without the limitation of a connection to the bar, and without a hassle of bringing athletes to the laboratory for testing or data processing after the testing.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, betaine has been linked to improving muscular endurance, strength, and power (31,55) and can be found in beetroot. Likewise, the polyphenols, quercetin and resveratrol, which are found in beetroot have, in some instances, been reported to increase aerobic capacity and stimulate mitochondrial biogenesis (20,44).…”
Section: Experimental Considerationsmentioning
confidence: 99%